PERSEPSI AUDITOR INTERNAL TERHADAP DETEKSI FRAUD - KURNIAWAN, YUANITA (: 2303-1719)
This discussion aims to provide an understanding of the internal auditor's perception of the risk of fraud. Internal auditors have a different background due to several factors such as: experience, including knowledge and competency in performing tasks, the conditions encountered, the level of professionalism that is owned, and so forth. This causes the difference in perception of the risk of fraud. Differences in perceptions of internal auditor to the risk of fraud also led to any different behavior from the internal auditor in response to the fraud that occurred. This led to the scope of the investigation also established internal auditor is different. Differences in perceptions of internal auditor to the risk of fraud should still do a check on the scope that gives confidence in the findings of fraud are generated, while running errands owned.